A Novel Sentinel Lymph Node Approach in Oral Squamous Cell Carcinoma - Kågedal, Åsa; Margolin, Gregori; Held, Cornelia; da Silva, Pedro F. N.; Piersiala, Krzysztof; Munck-Wikland, Eva; Jacobsson, Hans; Häyry, Valtteri; Cardell, Lars O. (Current Pharmaceutical Design, 2020)
Background: Occult metastases are common in patients with oral squamous cell carcinoma (OSCC) which is why elective neck dissection, adjuvant radiotherapy or watchful waiting have been treatment options after surgical removal of the primary tumour. Sentinel lymph node biopsy (SLNB) has lately emerged as a novel possibility in treatment planning. Objectives: To establish a reliable and clinically useful protocol for SLNB in staging/elective neck dissection in oral cancer. Methods: Fourteen consecutive patients with T1-T2 N0 oral cancer were enrolled when scheduled for elective neck dissection. Results: This study outlines various techniques for improving SLNB in head and neck cancer. After evaluation, a combination of techniques was found to constitute a reliable, clinically adaptable work concept. The suggested procedure starts with the pre-surgical injection of radioactive technetium 99Tcm carried on tilmanocept (Lymphoseek ®) at the tumour site. The radioactivity in the lymph node is then visualized preoperatively with Single Photon Emission Computed Tomography (SPECT/CT). Intraoperatively, indocyanine green (ICG) is injected and a sentinel node is visualized with near-infrared light. To support the sentinel node detection, the surgeon uses a hand-held gamma detection probe. This approach results in a reproducible and reliable detection of sentinel nodes. Conclusion: This paper presents a novel protocol for the identification of the sentinel node in the head and neck region. The protocol additionally enables the use of flow cytometry analysis of resected lymph nodes.
Keywords: tilmanocept